2019
DOI: 10.26487/hjbs.v1i1.189
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Role Ambiguity, Role Conflict, dan Role Overload terhadap Kinerja Pegawai Dimediasi Perilaku Cyber-loafing

Abstract: Cyberloafing merupakan kegiatan penggunaan internet yang berkaitan dengan hobi pegawai atau pengalihan kejenuhan atau stress kerja dengan berbagai hiburan yang ada diinternet pada jam kerja. Penelitian ini bertujuan untuk mengetahui Pengaruh Role Ambiguity, Role Conflict dan Role Overload Terhadap Kinerja Pegawai Dimediasi Perilaku Cyberloafing pada Biro Akademik dan Umum Universitas Sulawesi Barat. Pendekatan penelitian ini adalah pendekatan kuantitatif. Populasi dalam penelitian ini adalah pegawai pada Biro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
1
0
6
Order By: Relevance
“…Therefore, employees tend to do cyberloafing because it is considered the easiest to eliminate boredom, especially if it is supported by the availability of internet facilities on their respective computers and personal gadgets, but if employees have surfed the internet they do not return to their initial duties which are their responsibilities, resulting in negligence in settlement duty. This is in accordance with previous research conducted by Ahmad (2019) which showed that workload had a positive and significant effect on cyberloafing behavior. The difference in this study is in the Role Ambiguity variable because this variable is not included in the phenomenon that the researchers raised related to Cyberloafing behavior.…”
Section: Introductionsupporting
confidence: 93%
“…Therefore, employees tend to do cyberloafing because it is considered the easiest to eliminate boredom, especially if it is supported by the availability of internet facilities on their respective computers and personal gadgets, but if employees have surfed the internet they do not return to their initial duties which are their responsibilities, resulting in negligence in settlement duty. This is in accordance with previous research conducted by Ahmad (2019) which showed that workload had a positive and significant effect on cyberloafing behavior. The difference in this study is in the Role Ambiguity variable because this variable is not included in the phenomenon that the researchers raised related to Cyberloafing behavior.…”
Section: Introductionsupporting
confidence: 93%
“…Quantitatively and qualitatively, it will cause boredom and stress due to workload, and a feeling of power within oneself cannot solve the demands of tasks that cause fatigue. This is also to research conducted by [20], with the results of his research saying that there was a role overload among 64 employees of the Academic and General Bureau of the University of West Sulawesi, and the employees there said they were tired, so that the work produced decreased and there was no increase. This is evidenced by the results of hypothesis testing, which states that the alternative hypothesis is accepted, meaning that the higher the role overload affected by cyberloafing, the more employee performance will decrease.…”
Section: Description Of Role Overload In Muhammadiyahmentioning
confidence: 59%
“…Konflik peran berpengaruh signifikan positif terhadap perilaku cyberloafing (Sawitri, 2012). Temuan lain menunjukkan konflik peran juga berpengaruh signifikan terhadap perilaku cyberloafing (Ahmad, Parawansa, & Jusni, 2019;Hardiani, Rahardja, & Yuniawan, 2017;Herdiati et al, 2015;Nydia & Pareke, 2019), akan tetapi konflik peran dalam temuan lain tidak menunjukkan peran yang penting, dalam artian tidak ada hubunganya dengan perilaku cyberloafing Selain dipengaruhi oleh konflik peran, perilaku cyberloafing dipengaruhi oleh adanya ambiguitas peran yang didefinisikan sebagai bentuk ketidak pastian mengeni tugas dan harapan pekerjaan, kurangnya pedoman untuk perilaku kerja yang sesuai, dan ketidakpastian hasil perilaku. Ambiguitas peran berpengaruh signifikan positif terhadap perilaku cyberloafing (Sawitri, 2012).…”
Section: Latar Belakangunclassified
“…Ambiguitas peran berpengaruh signifikan positif terhadap perilaku cyberloafing (Sawitri, 2012). Adanya ambiguitas peran yang dirasakan oleh karyawan menyebabkan adanya perilaku cyberloafing (Ahmad et al, 2019;Herlianto, 2012;Lonteng et al, 2019;Nydia & Pareke, 2019). Temuan lain menunjukkan bahwa ambiguitas peran tidak menunjukkan adanya pengaruh terhadap perilaku cyberloafing (Herdiati et al, 2015).…”
Section: Latar Belakangunclassified